2016
DOI: 10.1128/jvi.01497-16
|View full text |Cite
|
Sign up to set email alerts
|

Vif Proteins from Diverse Human Immunodeficiency Virus/Simian Immunodeficiency Virus Lineages Have Distinct Binding Sites in A3C

Abstract: Lentiviruses have evolved the Vif protein to counteract APOBEC3 (A3) restriction factors by targeting them for proteasomal degradation. Previous studies have identified important residues in the interface of human immunodeficiency virus type 1 (HIV-1) Vif and human APOBEC3C (hA3C) or human APOBEC3F (hA3F). However, the interaction between primate A3C proteins and HIV-1 Vif or natural HIV-1 Vif variants is still poorly understood. Here, we report that HIV-1 Vif is inactive against A3Cs of rhesus macaques (rhA3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…The study revealed several key residues in the hydrophobic V-shaped groove formed by the 2 and 3 helices of A3C that facilitate Vif binding resulting in proteasome-mediated degradation of A3C [63]. We extended this finding and identified additional Vif interaction sites in 4 helix of A3C [64]. Other than a previous study that predicted putative DNA substrate binding pockets [52], biochemical and structural aspects of A3C enzymatic activity and their relevance for antiviral activity are not well investigated to date [3,4].…”
Section: Introductionmentioning
confidence: 75%
“…The study revealed several key residues in the hydrophobic V-shaped groove formed by the 2 and 3 helices of A3C that facilitate Vif binding resulting in proteasome-mediated degradation of A3C [63]. We extended this finding and identified additional Vif interaction sites in 4 helix of A3C [64]. Other than a previous study that predicted putative DNA substrate binding pockets [52], biochemical and structural aspects of A3C enzymatic activity and their relevance for antiviral activity are not well investigated to date [3,4].…”
Section: Introductionmentioning
confidence: 75%
“…Chimpanzee APOBEC3 (A3) expression plasmids (A3D, A3F, A3G and A3H) were provided by Michael Emerman [ 40 ], chimpanzee A3C plasmid was described recently [ 61 ]. Human A3s (A3A-A3H) were expressed by PTR600 vector with a carboxyl-terminal triple hemaggutinin (HA) tag [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…To generate the SIV Vif expression plasmids, Vif fragments from the following molecular clones: SIVcpz Ptt EK505 (DQ373065), Gab1 (X52154), MB897 (EF535994) and SIVcpz Pts TAN1 (AF447763), TAN2 (DQ374657) and SIVgor CP2139 (FJ424866) were amplified and inserted into pCRV1 by EcoRI and NotI . Vif expression plasmids of HIV-1 LAI, F-1, N-116 and O-127 were provided by Viviana Simon [ 33 , 61 ]. All SIVcpz Ptt MB897 Vif mutants were generated by overlapping PCR and cloned into pCRV1 without any tag, verified by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“… Schematic representation of A3-Vif interaction sites. ( A ) HIV-1 Vif binding sites in human A3C, A3F, A3G, and A3H [ 60 , 94 , 95 , 96 , 97 ]; ( B ) FIV, HIV-2, SIVmac, and SIVsmm Vifs binding sites in feline A3Z2, A3Z3, and A3Z2Z3, respectively [ 79 ]; ( C ) The human A3F, A3G, A3H, CUL5, CBF-β, and ElonginB/C binding sites in HIV-1 Vif (see review [ 98 ]); ( D ) The feline A3Z2, A3Z3, and CUL5 binding sites in FIV Vif [ 46 ]. FIV Vif domains that interact with additional cofactors and sites for oligomerization are not identified.…”
Section: Figurementioning
confidence: 99%